The features of organization of junior pupils' educational activities in the proses of foreign language study - Tamara Marchii-Dmytrash (Vasyl Stefanyk Precarpathian National University, 2017)
It is actualized the specificity of organization of primary school pupils' educationalactivities in the proses of foreign language study in the article. The components (target,motivative, semantic, procedural gameplay, effective, control-evaluative) and stages (preparative, executive, analytical-corrective) of organization of junior pupils'educationalactivity arejustified. The attention is paid to the leading role of foreign language teacherin themanagement of children's educational activities. Key words: educational activity, juniorpupils, elementary school, foreign language,organization, component, phase, foreign language teacher.